Metro Manila Urban Transportation Strategy Planning Project, corridor traffic management and truck operations implementation report, vol. 3, part b1 implementation ;project prioritization, refinement and adoption (Pak-Poy & Kneebone Pty Ltd, 1986)
This volume contains Implementation Reports for Corridor Traffic Management and Truck Operation Improvements Projects developed as part of the Metro Manila Urban Transportation Strategy Planning Project (MMUTSTRAP) Part B1 - Implementation Phase.